2022
DOI: 10.3389/fonc.2022.876487
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Granulomatous Lobular Mastitis and Breast Cancer Using Quantitative Parameters on Contrast-Enhanced Ultrasound

Abstract: ObjectiveTo investigate the Contrast-enhanced ultrasound (CEUS) imaging characteristics of granulomatous lobular mastitis (GLM) and the value of differentiating GLM from breast cancer.Materials and methodsThe study included 30 women with GLM (mean age 36.7 ± 5 years [SD]) and 58 women with breast cancer (mean age 48. ± 8 years [SD]) who were scheduled for ultrasound-guided tissue biopsy. All patients were evaluated with conventional US and CEUS prior to the biopsy. In both groups, the parameters of the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…It is sometimes difficult to distinguish between special types of mastitis (such as Plasma Cell Mastitis and Granulomatous Mastitis) and breast cancer, as these inflammatory lesions can sometimes appear very similar to breast cancer on gray‐scale ultrasound imaging. We found that Demetics often confuses inflammatory lesions with malignant lesions, which require further information with clinical symptoms, hematological tests and other imaging techniques (such as elastography and contrast‐enhanced ultrasound) 21,22 . We recommend that radiologists can be flexible in adjusting classification based on the individual circumstances of patients when diagnosing inflammatory breast lesions, rather than being misled by Demetics results.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is sometimes difficult to distinguish between special types of mastitis (such as Plasma Cell Mastitis and Granulomatous Mastitis) and breast cancer, as these inflammatory lesions can sometimes appear very similar to breast cancer on gray‐scale ultrasound imaging. We found that Demetics often confuses inflammatory lesions with malignant lesions, which require further information with clinical symptoms, hematological tests and other imaging techniques (such as elastography and contrast‐enhanced ultrasound) 21,22 . We recommend that radiologists can be flexible in adjusting classification based on the individual circumstances of patients when diagnosing inflammatory breast lesions, rather than being misled by Demetics results.…”
Section: Discussionmentioning
confidence: 93%
“…We found that Demetics often confuses inflammatory lesions with malignant lesions, which require further information with clinical symptoms, hematological tests and other imaging techniques (such as elastography and contrast-enhanced ultrasound). 21,22 We recommend that radiologists can be flexible in adjusting classification based on the individual circumstances of patients when diagnosing inflammatory breast lesions, rather than being misled by Demetics results. In addition, the histological components of breast adenosis are complex and can easily be compounded by other diseases.…”
Section: Characteristic Totalmentioning
confidence: 99%
“…It is readily available, easy to perform and a relatively inexpensive alternative to other modalities (MRI) used for perfusion assessment. It has been shown to overcome the limited signal-to-noise ratio and spatial resolution of Doppler USG in the evaluation of perfusion of the lesions and hence seems promising in the assessment of the perfusion characteristics of breast tumours [ 14 , 15 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both GLM and BC typically present as breast masses with indistinct borders and rm consistency, and may be accompanied by enlarged ipsilateral axillary lymph nodes. Although modern research has improved the non-invasive differential diagnosis of GLM and BC through various radiological techniques, such as sonogram radiomics model 22 , contrast-enhanced ultrasound 23 , ultrasound elastography 24 , deep-learning based AI automatic classi cation system 25 , and ARFI elastography 26 , the gold standard for diagnosing GLM still requires tissue biopsy. In some cases, multiple biopsies may be necessary for clinical differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%